Electromechanical impedance measurements for bone health monitoring through teeth used as probes of a Piezo-device - Cardona, Carlos I; Tinoco, Hector A; Marín-Berrio, Maribel L F; García-Grisales, Juliana; Gomez, Juan P; Roldan-Restrepo, Samuel I; Ortiz-Jimenez, Juliana (Biomedical physics & engineering express, 2020)
Bone is a dynamic biological tissue that acts as the primary rigid support of the body. Several systemic factors are responsible for pathologies that negatively affect its structural attributes. Although the bone is in continuous renewal by osteogenesis, metabolic diseases are the most common affectations that alter its natural equilibrium. Different techniques based on ionizing radiation are used for the bone diagnosis restrictively. However, if these are not used adequately, the application could present risks for human health. In this paper, it is proposed and explored a new technique to apply an early-stage diagnosis of bone variations. The technique evaluates bone structural conditions from the teeth (used as probes) by applying a structural health monitoring (SHM) methodology. An experimental procedure is described to identify the stiffness variations produced by mechanical drillings done in prepared bone samples. The identification is carried out applying the electromechanical impedance technique (EMI) through a piezo-actuated device in the frequency spectrum 5-20kHz. Three bone samples with incorporated teeth (three teeth, two teeth, and one tooth) were prepared to emulate a mandibular portion of alveolar bone-PDL (periodontal ligament)-tooth system. Piezo-device was attached to the crown of the tooth with an orthodontic bracket allowing the teeth to act as probes. The electrical resistance measurements were computed with an electrical decoupling approach that improved the detection of the drillings; it was due to the increment of the sensitivity of the signals. The results showed that the bone mass reduction is correlated with statistical indices obtained in specific frequency intervals of the electrical resistance. This work suggests the possibility of a future application addressed to a bone diagnosis in a non-invasive way.
Keywords: teeth; structural health monitoring; lidé; mandibula; periodontální vaz; Periodontal Ligament; electromechanical impedance; piezo-device; zuby; Mandible; kostní denzita; Humans; Tooth; Bone Density; bio-monitoring; elektrická impedance; bone; Electric Impedance